Raising potential growth after the crisis. A quantitative assessment of the potential gains from various structural reforms in the OECD area and beyond - Bouis, Romain; Duval, Romain (Paris, 2011)
"This paper provides an illustrative assessment of the impacts on potential GDP over a 5 to 10-year horizon of structural reform scenarios in the areas of product and labour markets, relying on existing OECD empirical studies. Results of simulations suggest that a gradual alignment of product market regulations to best practice in a broad range of non-manufacturing sectors could boost aggregate labour productivity levels by several per cent over the next decade in many OECD countries, and by over five per cent across most of continental Europe, as well as for the BRIICS. Relaxation of job protection legislation could also raise productivity growth for a while in many OECD and non-OECD G20 countries, although the effects are estimated to be smaller than those from product market reforms. In a scenario under which they would be phased in relatively quickly, labour market reforms in the areas of unemployment benefit systems, activation policies, labour taxes and pension systems could raise employment rates by several percentage points in a number of OECD countries over a 10-year horizon. Large continental European countries would have the largest benefits to reap from reforms. The overall potential GDP gain for the average OECD country from undertaking the full range of reforms considered here might come close to 10% at a 10-year horizon, indicating the presence of ample room for structural reforms to offset the permanent GDP losses from the recent crisis."